Asian and Oceanic Christianities in conversation : exploring theological identities at home and in diaspora - Kim, Hŭb-yŏng, 1949-; Matsuoka, Fumitaka.; Morimoto, Anri, 1956- (Studies in World Christianity and Interreligious Relations, 2011)
The old contrast between "universal" and "local" is now collapsing, but a new paradigm has yet to be defined. The contributors claim that the questions they raise will help redraw the lines of demarcation each in a unique way. Their collaborative result is a re-submission of the century-old question regarding "the essence of Christianity," and the readers will hear answers to this question resounding in polyphonic voices. The book will make a unique contribution to the scholarship by constructing a common forum connecting diasporic Asians and Oceanians who live and work in regions around the Pacific Ocean. Publication in the field of theology has been thick on the American side of the Pacific, and the agenda of discussion are shaped largely in accordance with the concerns of those living on the North-American continent and in British Isles. Theologians living on the other side of the Pacific, while in daily contact with the multi-religious realities that beg theological attention, sometimes lack means of engaging in sustained discussion with other theologians who are similarly struggling to gain insights into different cultural contexts. This book will provide a shared ground for reflection and discussion.